Extradition, Extraterritoriality, and Murder: Managing Portuguese Criminals in Chinese Port Cities - Chan,Catherine S. (2021)
Abstract Using a 1933 crime case known as the “Shanghai trunk murder” as a point of access, this study explores Portuguese extraterritoriality in China to shed light on the trans-border legal system of the Portuguese empire and the various purposes it served that went far beyond the pursuit of justice. The Portuguese legal system in China was integrated into a broader network that required legal processions concerning major criminal cases to move across the border and take place in Portuguese-controlled cities within and outside of China. Apart from revealing its trans-border features, this study also reveals through various extradition and criminal cases the political and diplomatic purposes that extraterritorial rights served for Portugal and the Macau administration, which went beyond the confines of justice.